Ethical and practical considerations in managing incidental findings in functional magnetic resonance imaging - Illes, Judy; Desmond, John E; Huang, Lynn F; Raffin, Thomas A; Atlas, Scott W (Brain and cognition, 2002)
Functional magnetic resonance imaging has emerged as a powerful tool for mapping the neurologic underpinnings of sensory, motor and cognitive function. Much of this evolution carries assumptions about the subject population under study and, in particular, the neurologic status of subjects entered into studies either as healthy controls or as belonging to a specific disease group. Recent reports of incidental MRI abnormalities in normal volunteers for fMRI studies have brought to attention a variety of practical challenges and ethical dilemmas for researchers, many of whom are not physicians and most of whom have no formal radiological training. We propose a minimum standard for consenting subjects in fMRI protocols, and consider strategies over the longer term that call for expert physician participation, archiving of incidental findings including false positives, and the adoption of guidelines for handling variation in neural activations or performance that appear outside expected norms.